Analysis of Digital Literacy Influenced by Reading Intensity, Use of Online Media and Role of Parents - Estu Niana Syamiya; Andi Yustira lestari Wahab; Ainia Lingziana Yuningsih (Universitas Negeri Padang, 2024)
This research aims to examine and determine the impact of online media usage, parental involvement, reading frequency, and gender on digital literacy. The study employs a quantitative approach using survey methods. The sample was selected through Simple Random Sampling, utilizing the Slovin formula with a 10% margin of error, resulting in a sample size of 70 students. Data was collected via questionnaires featuring checklists and rating scales, and analyzed using descriptive statistical analysis and multiple linear regression with the aid of IBM SPSS Version 25. The findings provide an overview of digital literacy among Ad-Da'wah Vocational School students in West Jakarta, indicating that there are more female students than male students. Online media usage does not significantly impact students' digital literacy. Similarly, parental involvement does not significantly affect the digital literacy of students at Ad-Da'wah Vocational School. The study highlights that digital literacy is crucial for increasing students' reading frequency, and that reading frequency significantly influences digital literacy among these students.